Crystal structure and revised chemical formula for burckhardtite, Pb2(Fe3+Te6+)[AlSi3O8]O6: a double-sheet silicate with intercalated phyllotellurate layers. (December 2014) - Christy, Andrew G.; Kampf, Anthony R.; Mills, Stuart J.; Housley, Robert M.; Thorne, Brent
Abstract: The crystal structure of burckhardite from the type locality, Moctezuma, Sonora, Mexico, has been refined to R1 = 0.0362 and wR2 = 0.0370 for 215 reflections with I > 2σ(I). Burckhardtite is trigonal, space group P3̄ 1m, with the unit-cell parameters a = 5.2566(5) Å, c = 13.0221(10) Å, V = 311.62(5) Å 3 and Z = 1 for the ideal formula unit Pb2(Fe 3+ Te 6+ )[AlSi3 O8 ]O6 . There is no long-range order of (Fe 3+, Te 6+ ) or (Al 3+, Si 4+ ). New microprobe data were used to estimate site scattering factors, and Raman spectroscopic data showed no evidence of O–H stretching bands. Burckhardtite is not closely related to the micas, as supposed previously, but is a double-sheet silicate in which the aluminosilicate anion resembles that of minerals such as cymrite and kampfite. The [(Fe 3+ Te 6+ )O6 ] 3– part of the structure is not bonded directly to the aluminosilicate layer, but forms a discrete anionic phyllotellurate layer that alternates with the [AlSi3 O8 ] – double sheets. Similar phyllotellurate layers are known from several synthetic phases. In burckhardtite, Pb 2+ cations intercalate between phyllosilicate and phyllotellurate layers, forming a Pb2 [FeTeO6 ] module that is topologically similar to a slab of the structure of rosiaite, Pb[Sb2 O6 ]. The crystal symmetry, structure, classification as a double-sheet silicate and chemical formula, including the determination of the 6+ valence of Te and absence of essential H2 O, are all new findings for the mineral.